Marriage versus Cohabitation: How Specialization and Time Use Differ by Relationship Type - Leslie S. Stratton (Global Labor Organization (GLO), 2023)
Relationships have changed dramatically in the last fifty years. Fewer couples are marrying, more are cohabiting. Reasons for this shift abound, but the shift may have consequences of its own. A number of models predict that those cohabiting will specialize less than those marrying. Panel data on time use - particularly housework time - as well as on the degree of specialization in more narrowly defined household tasks from the 2001-2019 waves of the Household, Income and Labour Dynamics in Australia survey are used to test this prediction. Panel analysis of reported time use data for men provides limited evidence of specialization in any type of relationship. The results for women are much stronger. Women who marry without first cohabiting increase their reported housework time more than those who enter cohabitations (by 3.7 hours versus 1.2 hours). The latter generally make up the difference if they marry. Expanding the analysis to other time uses yields some further evidence of specialization. Survey responses on the degree of specialization are more informative. The raw data show substantial intrahousehold specialization. Even controlling for a broad array of covariates, on average married couples specialize more than cohabiting couples. Furthermore, specialization increases when cohabiting couples marry. Interestingly, there does not appear to be a substantial tradeoff between tasks; partners who report specializing more on one task are more likely to report specializing on other tasks as well. Given the role couples have in family formation and the labor market, it is important to understand this intrahousehold behavior.
Keywords: J12; J16; I31; Z13; 330; Specialization; Time Use; Marriage; Cohabitation; Housework